Interests, initiatives, and influence: geopolitics in the Mekong Subregion - Teo, Sarah (2022)
The Mekong River’s importance is difficult to overstate. Originating from the Tibetan Plateau, the 4,350-kilometer river flows through China’s Yunnan Province and onward through Myanmar, Laos, Thailand, Cambodia, and Vietnam before draining into the South China Sea. At least 60 million people depend on the river for their lives and livelihoods. As the world’s largest inland fishery as well as a vital source for rice production and hydroelectricity to the riparian countries, the Mekong subregion has been progressively regarded as an area of strategic importance. This view has emerged alongside several trends. First, dam-building activities on the Mekong, intertwined with the worsening impact of climate change, pose an existential threat to the river’s ecosystem. Downstream communities that rely on the Mekong for survival have been particularly vulnerable to the river’s fluctuating water levels. Second, the effects of Sino-U.S. rivalry have seeped into the subregion, with Beijing and Washington stepping up their engagement with the riparian countries. The Mekong subregion is a crucial area for China’s Belt and Road Initiative and a key element of the United States’ “free and open Indo-Pacific” strategy.